ANALISIS KEPUASAN PELANGGAN TOKOPEDIA - Djuan Deus Ahuro Sibagariang (2022)
The ongoing Covid-19 pandemic has created a change in shopping activities from offline to online. There has been an increase in e-commerce players. In the era of the birth of e-commerce, there is an e-commerce that is having problems in the field of security, even though the number of people who use its services is increasing. This study aims to analyze and prove the effectiveness of online convenience, online trust, and online security on Tokopedia customer satisfaction. This study uses quantitative research with the use of a sample collection technique, namely purposive sampling. The selected population is Tokopedia users who live in Depok. The source of the data comes from the results of a questionnaire of 75 respondents. The analytical tool in this study is the SmartPLS 3 software. From the results of the study it was found: (1) there was a positive and significant influence on online convenience on Tokopedia customer satisfaction; (2) there is a positive and significant influence on online trust on Tokopedia customer satisfaction; (3) there is no significant effect on online security on Tokopedia customer satisfaction.